2014
DOI: 10.1109/tmag.2014.2327105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetostriction of NiFe Electroplated Film on the Noise of Fluxgate

Abstract: One of the sources of fluxgate noise is the noise originating in the magnetic core. Several parameters, such as anisotropy and shape, are traditionally studied and optimized to reduce the noise. In this paper, we show how the magnetostriction influences the noise of the fluxgate. We electroplated NiFe thin-film over a copper layer using different current density. By energy-dispersive X-ray spectroscopy we show that the mutual percentage of Fe and Ni in the film depends on the current density. As a result the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…6 shows the value of the power spectral density of the noise at 1 Hz (commonly used as a reference value for magnetometers) vs. the current density used in electroplating. As we expected [9] the noise is lowest at current density j 0 =16 mA/cm 2 , where the Ni 0.81 Fe 0.19 composition is obtained, and the magnetostriction is the lowest, whereas the noise increases as we reduce or increase the current density and therefore increase the magnetostriction.…”
Section: Effect Of the Anisotropy On The Noisesupporting
confidence: 59%
See 1 more Smart Citation
“…6 shows the value of the power spectral density of the noise at 1 Hz (commonly used as a reference value for magnetometers) vs. the current density used in electroplating. As we expected [9] the noise is lowest at current density j 0 =16 mA/cm 2 , where the Ni 0.81 Fe 0.19 composition is obtained, and the magnetostriction is the lowest, whereas the noise increases as we reduce or increase the current density and therefore increase the magnetostriction.…”
Section: Effect Of the Anisotropy On The Noisesupporting
confidence: 59%
“…The current density was changed in order to change the composition of the electroplated film. Current density j 0 =16 mA/cm 2 returns an ideal Ni 0.81 Fe 0.19 composition, whereas if we increase j the content of iron will increase and vice versa if the current density is decreased the content of nickel increases [9]. In this paper we tested current density up to 3 times larger than j 0 and down to 0.5 times j 0 .…”
Section: Manufacturing Of the Ringsmentioning
confidence: 98%
“…where M S is saturation magnetization evaluated from the B-H loop measured in the direction of applied stress. Technological details of the core preparation and technique to measure magnetostriction are described in [8].…”
Section: Experimental Partmentioning
confidence: 99%
“…It has been reported that low-noise soft magnetic materials have a relatively low Curie temperature, minimal magnetostriction, and minimal eddy current loss. (10,11) Ni 81 Fe 19 and cobalt-based amorphous materials, which are low-noise soft magnetic materials, are usually preferred for preparing the iron cores of fluxgates. Although changing the fabrication process and annealing the soft magnetic material used can reduce the noise of fluxgates, these methods are not effective in reducing the noise of micro-fluxgates.…”
Section: Introductionmentioning
confidence: 99%